Optimizing Beetroot Production Through Npk Fertilizer Application in Kabale Municipality, Kabale District - Robert Balibuganda (Uganda Christian University, 2025)
This research study, "Optimizing Beetroot Production through NPK Fertilizer Application in Kabale Municipality, Kabale District," aimed to determine how different application rates of NPK fertilizers affect beetroot growth and production. It was motivated by a need to enhance beetroot production among smallholders in this region through optimal nutrient use. It was intended to especially: (1) examine how different application rates of NPK fertilizers influence beetroot growth parameters such as plant height and number of leaves; (2) assess how application of NPK fertilizers influences yield of minor, medium, and large beetroot roots; and (3) determine the most financially successful application rates of fertilizers. A field trial was conducted in a Randomized Complete Block Design (RCBD) layout with five treatments: control (0 kg/ha), 50 kg/ha, 100 kg/ha, 150 kg/ha, and 200 kg/ha of NPK (17:17:17) fertilizer. Three replications were used for every treatment. Measurements were taken on plant height and number of leaves, while beetroot root yield was considered in categories with respect to weight and diameter, such as small, medium, and large. Statistical evaluation was performed using Analysis of Variance (ANOVA) to assess the level of differences among treatments. A cost-benefit analysis was conducted to identify the profitability associated with each fertilizer application rate. The results revealed that increasing rates of NPK fertilizer significantly enhanced beetroot growth and yield parameters. The highest plant height and number of leaves were observed at 150 kg/ha, with statistically significant differences (p < 0.001 for height and p = 0.014 for leaf number). The number of large-sized beetroot roots was significantly affected by NPK application (p = 0.0031), although the weight of these roots did not differ significantly across treatments (p = 0.877). The highest number of large-sized roots was recorded at 150 kg/ha, while medium-sized roots peaked at 100 kg/ha. The scatter and dotted graphs supported a strong positive relationship between fertilizer rate and root size up to the optimal level, beyond which diminishing returns were noted. Economic analysis indicated that the most profitable application rate was between 100 and 150 kg/ha, offering high yield returns while minimizing input costs. In conclusion, the study found that NPK fertilizer has a positive influence on beetroot growth and yield in Kabale Municipality. However, the benefits of fertilizer use reach a plateau beyond certain rates, indicating the importance of applying optimal rather than excessive amounts. It is therefore recommended that farmers in the region adopt moderate NPK application rates (100– 150 kg/ha) to maximize productivity and economic returns. Extension agents should train farmers on efficient fertilizer use and conduct on-farm demonstrations. Further research should investigate the long-term effects of NPK on soil fertility, beetroot nutrient content, and crop resilience under changing climatic conditions.
Undergraduate Research